Midbody: From Cellular Junk to Regulator of Cell Polarity and Cell Fate - Dionne, Lai Kuan (Curr Opin Cell Biol, 2015)
At late mitosis, the mother cell divides by the formation of a cleavage furrow, leaving two daughter cells connected by a thin intercellular bridge. During ingression of the cleavage furrow, the central spindle microtubules are compacted to form the structure known as the midbody (MB). The MB is situated within the intercellular bridge, with the abscission site sometimes occurring on one side of the MB. As a result of this one-sided (asymmetric) abscission, only one daughter cell can inherit the post-mitotic MB. Interestingly, recent studies have identified post-mitotic MBs as novel signaling platforms regulating stem cell fate and proliferation. Additionally, MBs were proposed to serve a role of polarity cues during the neurite outgrowth and apical lumen formation. Thus, abscission and MB inheritance is clearly a highly regulated cellular event that can affect development and various other cellular functions. In this review we discuss the latest findings regarding post-mitotic MB functions, as well as the machinery regulating MB inheritance and accumulation.